Performance status versus anatomical recovery in metastatic disease: The role of palliative radiation treatment. (September 2016) - Reginelli, Alfonso; Silvestro, Giustino; Fontanella, Giovanni; Sangiovanni, Angelo; Conte, Mario; Nuzzo, Iolanda; Di lecce, Ada; Martino, Antonia; Grassi, Roberta; Murino, Paola; Cappabianca, Salvatore
Abstract: Metastatic disease is a common complication of the most advanced malignancies. It may compromise the patients' quality of life, often posing a greater risk than the primary disease itself. Currently, several different therapeutic approaches are available to palliate or cure (single metastasis with primary neoplasm under control – radical surgery) secondary disease. In particular, radiation therapy is widely used, as it often leads to full or at least partial functional recovery, depending on the number and location of metastases. The aim of our study was to evaluate whether clinical improvement subsequent to radiation therapy may be related to anatomical recovery of the site of metastasis in cancer patients with metastatic disease. Given the heterogeneity of the diseases considered and the general complex conditions of the patients, a single method could not be used to evaluate the response to radiation treatment and its correlation with the performance status (PS). Thus, depending on the specific disease being assessed, we divided the patients into different groups. Patients in the same group were followed up with the same methods. This correlation was noted in a very high percentage of patients, predominantly in patients with vertebral and brain metastases. Moreover, we investigated the use of magnetic resonance imaging (MRI)-diffusion weighted imaging (DWI) in the study of spinal metastases. We propose its use in the local evaluation of vertebral secondary lesions, both in the diagnostic phase and during the assessment of treatment efficacy.